Assessing the Expectations and Limitations of ASEAN-EU Counter-Terrorism Cooperation - Ali A. Wibisono; Aisha R. Kusumasomantri (JAS (Journal of ASEAN Studies), 2020)
This research examines the inter-regional security cooperation between ASEAN and the EU with a specific focus on counterterrorism. The research methods are based on a comparison of regional counterterrorism governance between the two regions and a close reading of Plan of Actions for the enhancement of ASEAN-EU relations documents from 2007 to 2018. The results show that CT cooperation is about facilitating a more comprehensive security governance cooperation where European standards and experience are transferred to Southeast Asia for purposes of regional security and diplomatic relations. In addition, this research also shows that EU-ASEAN CT cooperation has not been geared specifically to combat radicalism, or as part of a Counter Violent Extremism program; rather, the inter-regional cooperation has mainly focused on building a common normative framework in responding to terrorism within the corridor of democracy and preempting the terrorist networks from exploiting connectivity networks. Finally, implementation of security and political cooperation between the EU and ASEAN tend to rely on the existing extra-regional dialogue fora within ASEAN as well as direct engagement between the EU and third parties comprising each of the ASEAN states.